Metal–organic framework preparation using magnetic graphene oxide–β-cyclodextrin for neonicotinoid pesticide adsorption and removal. (1st November 2017) - Liu, Guangyang; Li, Lingyun; Xu, Donghui; Huang, Xiaodong; Xu, Xiaomin; Zheng, Shuning; Zhang, Yanguo; Lin, Huan
Highlights: A novel magnetic copper-based MOF was successfully prepared using Fe4 O3 –GO–β-CD. M-MOF was used for the adsorption and removal of neonicotinoid insecticides. Fe4 O3 –GO–β-CD has a thin single-layer structure with M-MOF coated on its surface. The results suggest that M-MOF gives high and fast adsorption of target insecticides. Abstract: A novel magnetic copper-based metal–organic framework (M-MOF) was prepared using a Fe4 O3 –graphene oxide (GO)–β-cyclodextrin (β-CD) nanocomposite as the magnetic core and support, and used for adsorption and removal of neonicotinoid insecticide pollutants from aqueous solution. M-MOF characterization suggested that 1 Fe4 O3 –GO–β-CD consisted of a thin single layer with anchored Fe3 O4 . The M-MOF was coated on the Fe4 O3 –GO–β-CD surface. The M-MOF had a large Brunauer–Emmett–Teller surface area (250.33 m 2 g −1) and high super-paramagnetism with saturation magnetization of 10.47 emu g −1 . Adsorption model analysis showed that the equilibrium data for thiacloprid fitted Langmuir monolayer adsorption and the other insecticides tested showed Freundlich bimolecular layer adsorption. The results show that M-MOF is a promising hybrid adsorbent for rapid removal of neonicotinoid insecticide pollutants from environmental waters.